2021
DOI: 10.1364/ol.424619
|View full text |Cite
|
Sign up to set email alerts
|

Full-mode characterization of correlated photon pairs generated in spontaneous downconversion

Abstract: Spontaneous parametric downconversion is the primary source to generate entangled photon pairs in quantum photonics laboratories. Depending on the experimental design, the generated photon pairs can be correlated in the frequency spectrum, polarization, position-momentum, and spatial modes. Exploring the spatial modes’ correlation has hitherto been limited to the polar coordinates’ azimuthal angle, and a few attempts to study Walsh mode’s radial states. Here, we study the full-mode correlation, on a Laguerre–G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…the ones in refs. [55,67]), in the context of benchmarking highly correlated quantum states. We achieved an enhancement on the reconstruction time up to 3 order of magnitude with high fidelities for the biphoton states, obtaining an average fidelity equal to 87%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the ones in refs. [55,67]), in the context of benchmarking highly correlated quantum states. We achieved an enhancement on the reconstruction time up to 3 order of magnitude with high fidelities for the biphoton states, obtaining an average fidelity equal to 87%.…”
Section: Discussionmentioning
confidence: 99%
“…In these sources, the two-photon wavefunction strongly depends on the shape of the pump laser used to induce the down-conversion process [53]. The most used approach to reconstruct the biphoton state emitted by a nonlinear crystal in literature is based on projective techniques [18,[54][55][56][57]. This method has drawbacks for what concern measurement times since it needs successive measurements on non-orthogonal bases and for the signal loss due to diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…Note: We have recently become aware of a related work [41] that characterised LG radial mode entanglement through full quantum state tomography in state spaces with local dimension 4.…”
Section: Discussionmentioning
confidence: 99%
“…While the precise description of the full transverse structure of light requires both indices (ℓ and p), the generation and detection of LG modes in the quantum domain initially focused on their azimuthal component [10,29], with early experiments demonstrating their use in quantum communication and entanglement (please see [4] for a review of these). The 'forgotten' radial quantum number p [33] has emerged in recent years as the subject of several theoretical investigations [34][35][36][37], with various experimental demonstrations of quantum radial correlations in the transverse field of photons produced through spontaneous parametric down-conversion (SPDC) [38][39][40][41]. These studies have shown that although perfect azimuthal correlations can be easily observed due to the conservation of OAM, entanglement in the radial part is only available when the the pump and detected mode waists are finely tuned [34,42].…”
Section: Introductionmentioning
confidence: 99%
“…For example, spatial light modulators (SLMs) can be placed in the pump beam or the photon pairs path to manipulate their spatial properties. They enable tailoring of the spatial entanglement between photons propagating in free space by manipulating their orbital angular spectrum [14][15][16][17][18][19][20], by shaping momentum-position correlations [21][22][23] or by tuning the pump spatial coherence [24,25]. In addition, they can also be used to control photon pair propagation through complex media such as multimode fibers [26][27][28] and scattering layers [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%